When the drugs don't work: treatment-resistant schizophrenia, serotonin and serendipity. Issue 1 (January 2018) - Lowe, Penelope; Krivoy, Amir; Porffy, Lilla; Henriksdottir, Erna; Eromona, Whiskey; Shergill, Sukhwinder S.
Treatment-resistant schizophrenia is a serious clinical problem. We adopt a systems-level approach positing a greater role for cognitive control mechanisms in the development of psychotic symptoms and illustrate the clinical application of this via a case report of treatment-resistant patients treated successfully with adjunct pro-cognitive serotonergic medication.